Effect of Teki Grass Extract (Cyperus rotundus) on the Growth of Green Beans (Vigna radiata) and Red Spinach (Amaranthus dubius) - Azwir Anhar; Monica, Della Trya; Tazri, Mufidah Insani; Oktaviani, Mutia; Wulandari, Tesya; Violita, Violita (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Weeds are plants that humans try to manage because they inhibit the growth of cultivated plants or are harmful to human interests. This study aims to evaluate the effect of teki grass extract (Cyperus rotundus) on the growth of green beans (Vigna radiata) and red spinach (Amaranthus dubius). The research method used a completely randomized design (CRD) with two extract concentration treatments (30% and 50%) applied to both plants. The results showed that treatment with teki extract significantly affected plant growth, with a decrease in height and fresh weight at higher concentrations. The allelopathic effect of the teki extract inhibited the vegetative growth of mung beans and red spinach, indicating that this extract has potential as a bioherbicide agent.